Influence of Body Posture and Electrode Placement on the Measurement of Electrocardiogram Using Textile Electrodes - Sadatamin, Delaram; Culjak, Ivana; Sadatamin, Saba; Piper, Bryan; Garnier, Baptiste; Yadollahi, Azadeh (CMBES Proceedings, 2024)
Abstract— Wearable technology has become popular in recent years due to its convenient ability to be integrated into our everyday lives. These tools can collect a wide range of data and help us to observe and manage various aspects of our health more closely. Smart clothing is a wearable that can track physiological signals, such as electrocardiogram (ECG) conveniently, remotely, and continuously. The quality of the captured ECG signal depends on various factors such as body posture and electrode placement. This study’s main objective is to investigate these factors’ influence on the ECG signal quality. Three healthy adults participated in the study. ECG signal was captured with both gold standard gel electrodes and dry textile electrodes simultaneously. The heart rate (HR) values from both gel and textile electrodes were calculated in different body postures and with different electrode placements. Statistical analysis was done to see how accurately the textile captured ECG in comparison with the gold standard in different body postures and with different electrode placements. Furthermore, the absolute error between gel and textile measurements was calculated in different body postures and electrode placements to see which combinations give more accurate HR compared to the gold standard. The early results indicate that electrode placement and body posture interact to affect HR measurement accuracy. Future work to gather more data is being done to achieve additional statistical power to draw definitive conclusions regarding the influence of electrode placement and body posture on ECG accuracy. Keywords— Smart Textiles, ECG Monitoring, Heart Rate, Electrode Placement, Body Posture